2009
DOI: 10.1117/12.804281
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influence on non-invasive blood glucose measurement

Abstract: Regular monitoring of blood sugar level is important for the management of diabetes. The Near-Infra-Red (NIR) spectroscopy method is a promising approach and this involves some form of contact with the body skin. It is noted that the skin temperature does fluctuate with the environment and physiological conditions and the temperature has an influence on the glucose measurement. In this paper, in-vitro and in-vivo investigations on the temperature influence on blood glucose measurement were studied. The in-vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In human non-invasive blood component measurement (NBCM) using near-infrared spectroscopy, fluctuations in skin temperature are big and cannot be ignored 1 . Affected by the physiological state of the human body, the temperature of the skin is fluctuating inevitably.…”
Section: Introductionmentioning
confidence: 99%
“…In human non-invasive blood component measurement (NBCM) using near-infrared spectroscopy, fluctuations in skin temperature are big and cannot be ignored 1 . Affected by the physiological state of the human body, the temperature of the skin is fluctuating inevitably.…”
Section: Introductionmentioning
confidence: 99%
“…Among many, optical spectroscopic methods have attracted a fair amount of attention (7)(8)(9)(10)(11)(12)(13)(14). While near-infrared (NIR) absorption spectroscopy has demonstrated some potential, extracting glucosespecific features in the presence of many confounding signals from in vivo measurements has been challenging (15)(16)(17)(18)(19)(20)(21). NIR absorption features of glucose in overtone and combination bands are broad and interfere with the absorption of other chromophores in tissue.…”
Section: Introductionmentioning
confidence: 99%
“…5 Zhang et al studied temperature influence on noninvasive blood glucose measurement and the result showed that sample temperature had significant influence on water absorption, which significantly affects the glucose absorption measurement. 6 On the other hand, human tissue is the turbid medium. Changes in temperature can lead to changes both in absorption and scattering properties, thus affecting or even hiding the information of glucose.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Zhang et al took the temperature of human tissue surface into consideration, which can significantly improve blood glucose prediction accuracy. 6 Chen et al used a referencewavelength-based method to correct the spectra, which can effectively reduce the influence of temperature variations on the sample spectra. 12 Yang et al proposed a floating reference method, 13 which is based on the mechanism that the diffuse reflectance is not affected by the glucose concentration variation at a special radial distance.…”
Section: Introductionmentioning
confidence: 99%